PENDIDIKAN MENTAL ISLAM PERSPEKTIF PESANTREN SUMBER PENDIDIKAN MENTAL AGAMA ALLAH (SPMAA) UNTUK MENINGKATKAN POTENSI SANTRI DALAM BERKONTRIBUSI PEMBERDAYAAN MASYARAKAT - Khasanah, Uswatun (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2025)
Mental and spiritual education is highly effective in today's educational world. With strong mental and spiritual foundations, students can be guided toward glory and success. The Sumber Pendidikan Mental Agama Allah (SPMAA) Islamic boarding school is one of the educational institutions that operates in the fields of social, education, and environment. The focus of education at SPMAA is on instilling Islamic values through various life practices, strengthening the faith and mentality of the students, and training them as the nation's future generation, who will contribute to community empowerment. The purpose of this research is to explore how SPMAA instills Islamic values in its students to enhance their mental and spiritual development, enabling them to contribute to community empowerment. This research uses a descriptive qualitative method. The findings of the study include: first, the Mental Education at SPMAA, which involves instilling Islamic values in students, has produced cadres who are ready to engage with society as agents of community empowerment. Second, the education system at SPMAA, compatible with the lifelong learning system, creates broader and more varied learning media and practices. Third, SPMAA is not only focused on Islamic education but also on social and environmental issues